2022
DOI: 10.1212/wnl.0000000000200883
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Optical Coherence Tomography Criteria and Machine Learning in Multiple Sclerosis and Optic Neuritis Diagnosis

Abstract: Background and Objectives:Recent studies have suggested that inter-eye differences (IEDs) in peripapillary retinal nerve fiber layer (pRNFL) or ganglion cell+inner plexiform (GCIPL) thickness by spectral-domain optical coherence tomography (SD-OCT) may identify people with a history of unilateral optic neuritis (ON). However, this requires further validation. Machine learning classification may be useful for validating thresholds for OCT IEDs and for examining added utility for visual function tests, such as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 16 publications
4
27
0
Order By: Relevance
“…Similarly, Kenney et al [ 65 ] suggested using ML classification to set thresholds for OCT inter-eye differences (IEDs) to aid in MS diagnosis. They measured the peripapillary RNFL and ganglion cell + inner plexiform (GCIPL) thicknesses using spectral-domain optical coherence tomography (SD-OCT).…”
Section: Related Studiesmentioning
confidence: 99%
“…Similarly, Kenney et al [ 65 ] suggested using ML classification to set thresholds for OCT inter-eye differences (IEDs) to aid in MS diagnosis. They measured the peripapillary RNFL and ganglion cell + inner plexiform (GCIPL) thicknesses using spectral-domain optical coherence tomography (SD-OCT).…”
Section: Related Studiesmentioning
confidence: 99%
“…32,34 Machine learning based classification of eyes with ON history utilizing standard OCT parameters has been promising. 35 However, not all ON lead to measurable neuroaxonal damage, and in a previous study about 15% of patients do not suffer relevant damage during an ON episode. 36 This limits the value of methods relying on absolute OCT parameter thickness or inter-eye differences.…”
Section: Discussionmentioning
confidence: 90%
“…Clinically meaningful cut‐off values may be defined in comparison to healthy controls 20 or based on large reference studies with MS‐derived OCT measures 32,34 . Machine learning based classification of eyes with ON history utilizing standard OCT parameters has been promising 35 . However, not all ON lead to measurable neuroaxonal damage, and in a previous study about 15% of patients do not suffer relevant damage during an ON episode 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The only study to date involving a large dataset has been recently conducted by Kenney et al [16]. The authors used Cirrus high-definition OCT and converted Spectralis HP-OCT measurements of the pRNFL and GCL+ layers.…”
Section: Machine Learning In the Diagnosis Of Ms Usable Solutionsmentioning
confidence: 99%